Underwater friction power generation solid-liquid composite friction material and preparation method thereof

CN122978518APending Publication Date: 2026-10-27CHINA CONSTR SEVENTH ENG DIVISION CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611157943.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但封装方案存在难以克服的固有缺陷:刚性封装结构机械强度高,但厚重的外壳会增大结构惯性,提高启动阈值,削弱器件对微弱水流的响应灵敏度,且深水高压下长期存在密封疲劳失效风险;柔性封装结构虽提升了低频响应能力,但在高静水压作用下内部气隙易被压缩,摩擦层无法正常分离,输出性能随水深增加急剧衰减,无法适配深水应用场景

Benefits of technology

[0036]本发明可作为核心摩擦层应用于各类水下摩擦纳米发电机、水下自驱动流体传感器件中,适配滑动、接触-分离、滚动等多种工作模式,相对于现有水下摩擦发电材料,具备以下显著的技术进步:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978518A_ABST
    Figure CN122978518A_ABST
Patent Text Reader

Abstract

The application discloses a kind of solid-liquid composite friction materials for underwater friction power generation and preparation method thereof, belong to the technical field of friction nanogenerator functional materials.The solid-liquid composite friction material for underwater friction power generation is formed by hydrophobic oleophilic porous carrier and insulating liquid dielectric, and the insulating liquid phase is stably bound inside three-dimensional pore network by capillary force;When pressure, pore shrinkage, liquid phase exudes to form liquid film to realize interface conversion;After pressure is removed, pore rebounds, and liquid phase is sucked back to the inside of pore, and the process is completely reversible.The material completely breaks through the shielding of underwater double electric layer, and the transferred charge amount under 3cm 2 Contact area can reach 38.67nC, which is more than 5 times of pure solid material;And liquid phase binding capacity is strong, and the performance attenuation of continuous operation under open water flow is less than 2%, and the long-term stability is excellent.The preparation process of the application is simple, low in cost, suitable for various working modes, and can be widely applied to various underwater friction nanogenerator and self-driven sensor devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of functional materials for triboelectric nanogenerators and underwater energy harvesting materials, specifically relating to a solid-liquid composite triboelectric material for underwater triboelectric power generation based on a porous capillary constraint mechanism and its preparation method. Background Technology

[0002] Triboelectric nanogenerators (TGNs) convert mechanical energy into electrical energy based on the coupling effect of triboelectric charging and electrostatic induction. They exhibit significant advantages in low-frequency, irregular mechanical energy harvesting and are widely used in various scenarios such as wind power, hydropower, and human motion energy harvesting. Underwater energy harvesting is a crucial application area for TGNs, showing great potential in areas such as powering marine IoT nodes and underwater self-propelled sensing. However, the underwater environment differs fundamentally from the air environment: when solid triboelectric materials are directly exposed to water, the electrostatic charge on the solid surface attracts counterions from the water to accumulate at the interface, forming a dense double-layer structure. This generates a strong electrostatic shielding effect, leading to a significant decrease in the output performance of the TGN. Existing research shows that the output performance of traditional pure solid triboelectric materials underwater is typically only 10%-20% of that in air, which is insufficient for practical applications. Double-layer shielding has become a core bottleneck restricting the development of underwater TGNs.

[0003] To overcome the challenge of underwater double-layer shielding, researchers have explored various technical approaches, with encapsulation and interface control being the two main directions. Encapsulation isolates the power generation unit from the external water body through a physical sealing structure, keeping the friction interface in a dry air environment and fundamentally avoiding the effects of the double layer. However, encapsulation has inherent drawbacks: rigid encapsulation structures offer high mechanical strength, but the heavy shell increases structural inertia, raises the start-up threshold, weakens the device's response sensitivity to weak water flow, and poses a risk of long-term seal fatigue failure under deep-water pressure; flexible encapsulation structures, while improving low-frequency response, are prone to internal air gap compression under high hydrostatic pressure, preventing proper separation of the friction layer and causing a sharp decline in output performance with increasing water depth, making them unsuitable for deep-water applications. Neither type of encapsulation can simultaneously achieve both deep-water pressure resistance and energy conversion efficiency.

[0004] Interface control schemes dynamically alter the interface composition by introducing a second-phase medium, achieving reversible control of the electric double layer in open water environments. Early research primarily focused on gaseous medium control, using methods such as bubble impaction and slippage to displace the interfacial water phase, temporarily removing the electric double layer shield to generate electricity. However, gaseous media have low dielectric strength, are easily dissolved and deformed in high-pressure underwater environments, and the bubble volume shrinks significantly with increasing water depth, leading to a sharp decline in power generation performance. Furthermore, the bubbles are easily dispersed and lost with the water flow, resulting in poor long-term operational stability and failing to meet the requirements of engineering applications.

[0005] Building upon this foundation, interface transition schemes mediated by insulating liquid dielectrics have gradually gained attention. By replacing the water phase at the interface with an insulating liquid phase that is immiscible with water, the double-layer structure can be physically disrupted, electrostatic shielding can be removed, and the liquid phase medium exhibits higher dielectric strength and more stable physical properties compared to the gas phase medium. However, existing liquid phase schemes generally employ an open liquid bridge structure, where the liquid medium relies solely on surface tension to maintain itself at the friction interface, resulting in three major drawbacks: First, poor liquid phase retention; under open water flow, it is easily dispersed and lost, leading to rapid degradation of power generation performance over time and insufficient long-term stability. Second, poor controllability of the interface morphology; the liquid bridge is prone to deformation and breakage under shear forces, resulting in large fluctuations in the output signal and difficulty in ensuring consistency and reliability. Third, it can only adapt to simple planar sliding or contact-separation modes, and cannot adapt to complex motion modes such as rolling and multi-directional impact, limiting its application scenarios.

[0006] To date, a systematic design framework for underwater solid-liquid composite friction materials has not been established in this field. Existing research only reaches the preliminary verification level of liquid phase interface phenomena, failing to address the balance between "stable liquid phase confinement" and "dynamic interface transformation" at the material structure level: if the liquid phase confinement force is excessively strengthened, the liquid phase will be difficult to permeate and form an effective interface transformation, resulting in decreased output performance; if the confinement force is reduced to ensure the interface transformation effect, the liquid phase is prone to leakage, leading to insufficient stability. Furthermore, existing solutions lack mature, controllable, and mass-producible preparation processes, resulting in poor material performance consistency and difficulty in supporting engineering applications. In addition, existing underwater friction materials generally suffer from single-function limitations, failing to simultaneously achieve high output performance, long-term operational stability, and multi-mode adaptability.

[0007] In summary, existing underwater triboelectric power generation materials consistently face multiple irreconcilable contradictions: pure solid materials suffer from the contradiction of "strong double-layer shielding but low output performance"; open liquid-phase solutions face the contradiction of "high interface conversion efficiency but poor medium retention stability"; and engineering applications face the contradiction of "performance requirements and lifespan requirements being mutually exclusive." How to enable triboelectric power generation materials to simultaneously possess stable liquid-phase retention capabilities, efficient charge output performance, and long-term operational reliability in open water environments, while overcoming the multiple contradictions of strong double-layer shielding, easy liquid-phase medium loss, and rapid degradation of power generation performance in underwater triboelectric materials, is a core material technology challenge that urgently needs to be solved in this field.

[0008] It should be noted that the analysis of the above technical information is the result of creative labor. The detailed description of it in the background section is only intended to deepen the understanding of the non-obviousness of the overall background of this application by those skilled in the art, and should not be regarded as an admission or in any form an implication that the above technical information constitutes prior art known to those skilled in the art. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide a solid-liquid composite friction material for underwater triboelectric power generation and its preparation method. The technical problem to be solved is: how to enable triboelectric power generation materials to simultaneously possess stable liquid phase retention capability, efficient charge output performance, and long-term operational reliability in an open water environment, and overcome the multiple contradictions of strong double-layer shielding, easy loss of liquid phase medium, and rapid degradation of power generation performance in underwater triboelectric materials.

[0010] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0011] A solid-liquid composite friction material for underwater triboelectric power generation includes a hydrophobic and oleophilic porous carrier and an insulating liquid dielectric.

[0012] The insulating liquid dielectric is adsorbed within the three-dimensional pore network of the hydrophobic and oleophilic porous carrier and bound within the pore structure by capillary forces. When the material is under pressure, the pores contract and deform, and the insulating liquid dielectric seeps out to the material surface to form a continuous liquid film. After the pressure is removed, the pores rebound, and the insulating liquid dielectric is drawn back into the pores under capillary force. In other words, the material is a composite of a hydrophobic and oleophilic porous carrier and an insulating liquid dielectric. The insulating liquid dielectric is adsorbed within the three-dimensional pore network of the hydrophobic and oleophilic porous carrier through an impregnation process and stably bound within the material by capillary forces. The material as a whole possesses elastic deformation capability. When under pressure, the pores contract, and the internal insulating liquid dielectric is squeezed out to the material surface, forming a continuous and uniform liquid film. After the pressure is removed, the porous carrier rebounds elastically, and the pores expand, generating capillary suction that draws the surface insulating liquid dielectric back into the pores, achieving reversible release and recovery of the liquid phase.

[0013] Working principle explanation:

[0014] Capillary binding stabilization mechanism: The hydrophobic and oleophilic porous carrier contains a large number of interconnected micro- and nano-sized pores, forming a three-dimensional capillary network. According to the capillary force formula, the smaller the pore radius, the stronger the capillary binding force on the liquid phase. Due to the hydrophobic and oleophilic properties of the carrier material, the insulating liquid dielectric can be completely wetted within the pores, generating strong capillary adsorption forces that stably bind the liquid phase within the three-dimensional network; while the aqueous phase, due to its hydrophobic properties, cannot enter the porous structure and will not displace or dilute the internal insulating liquid dielectric. This structural design fundamentally solves the problem of open liquid bridges being easily dispersed and lost by water flow, enabling the material to maintain the long-term stability of the liquid phase medium even in open water flow environments.

[0015] Dynamic Reversible Response Mechanism: The porous carrier possesses excellent elastic deformation capabilities, allowing for reversible changes in pore volume under external forces. When subjected to contact pressure or shear force, the pores are compressed, reducing the internal space and forcing the insulating liquid dielectric to the material surface, where it spreads to form a continuous liquid film at the friction interface, providing a liquid medium for interface transition. When the external force is removed, the carrier recovers its original shape through its own elasticity, and the pore volume expands, generating negative pressure. Combined with capillary forces, this draws the surface liquid phase back into the pores, restoring the interface to a solid-water contact state. This dynamic process is completely reversible and can respond synchronously to periodic changes in external forces without requiring additional drive or control, naturally adapting to the reciprocating motion mode of a triboelectric generator.

[0016] Interfacial power generation enhancement mechanism: When this material is used as a triboelectric layer in an underwater triboelectric nanogenerator, the insulating liquid dielectric that seeps out under pressure comes into contact with the solid dielectric layer on the opposite side. This rapidly displaces water molecules and adsorbed cations at the interface, transforming the original solid-water interface into a solid-insulating liquid dielectric interface. This physically disrupts the double-layer structure, completely eliminating the electrostatic shielding effect. At this point, the charge transfer efficiency at the triboelectric interface is significantly improved, and the output performance can approach the level of air, fundamentally solving the output attenuation problem caused by underwater double-layer shielding. Compared to pure solid triboelectric materials, the charge output performance can be improved by several times to an order of magnitude.

[0017] Furthermore, the hydrophobic and oleophilic porous carrier is one of meltblown polypropylene porous network, polytetrafluoroethylene microporous membrane, and polyurethane foam, preferably meltblown polypropylene porous network.

[0018] All three carriers possess hydrophobic and oleophilic properties, enabling capillary adsorption and binding of insulating liquid dielectrics, but their overall performance differs. Polytetrafluoroethylene (PTFE) microporous membranes exhibit the best chemical stability, but suffer from weak elastic deformation, limited pore compression, insufficient liquid phase release, and high cost. Polyurethane foam boasts high porosity and large liquid storage capacity, but its mechanical strength is relatively low; it is prone to plastic deformation under long-term repeated compression, resulting in a limited service life. Meltblown polypropylene, with its three-dimensional network structure formed by randomly stacked ultrafine fibers, combines moderate porosity, excellent elastic deformation, and good mechanical strength. It releases the liquid phase fully under pressure and rebounds rapidly after decompression. Furthermore, its raw material cost is low and it is easy to process, making it the carrier with the best overall performance. Experimental verification shows that under the same test conditions, the transferred charge of the meltblown polypropylene-based composite friction material can reach 38.67 nC, significantly higher than the other two carrier materials, and it exhibits the best long-term operational stability.

[0019] Furthermore, the insulating liquid dielectric is a perfluorinated insulating liquid that is immiscible with water, preferably perfluorotributylamine.

[0020] The strong electronegativity of fluorine atoms in perfluorinated liquid molecules endows the materials with excellent electrical insulation and chemical inertness. They are completely immiscible with water and have a strong interfacial affinity with fluorinated solid materials, allowing them to spread rapidly on solid surfaces to form a uniform liquid film. Perfluorotributylamine, as a typical perfluorinated liquid, has a relative permittivity of only 1.9, extremely low interfacial polarization loss, and higher charge transfer efficiency. Simultaneously, its low surface energy results in minimal residue during the reciprocating motion of the friction interface, preventing the formation of a persistent shielding oil film and ensuring good output stability. Experimental comparisons show that the overall power generation performance of perfluorotributylamine is significantly superior to other insulating liquids such as alkanes, silicone oils, and vegetable oils, making it the optimal liquid phase medium for this material system.

[0021] Furthermore, the static water contact angle of the hydrophobic and oleophilic porous carrier is greater than 120°, and the contact angle with the insulating liquid dielectric is close to 0°.

[0022] Differences in wettability are fundamental to achieving capillary adsorption and interfacial displacement. A water contact angle greater than 120° indicates strong hydrophobicity of the carrier, preventing water from penetrating into the pores and diluting or displacing the insulating liquid phase, thus ensuring the structural stability of the material in underwater environments. Conversely, a contact angle close to 0° with the insulating liquid dielectric indicates strong oleophilicity of the carrier, allowing the liquid phase to spread and wet completely within the pores, generating maximum capillary adsorption force and achieving efficient confinement and rapid transport of the liquid phase. This differentiated design of wettability ensures the material's core function of "oil locking and drainage," forming the physical property basis for long-term stable operation. Taking the preferred meltblown polypropylene as an example, its static water contact angle can reach 138.4°, completely wetting perfluorotributylamine and perfectly matching the aforementioned wettability requirements.

[0023] Furthermore, the thickness of the hydrophobic and oleophilic porous carrier is 1.0-3.0 mm, and the porosity is 60%-85%; the saturated adsorption capacity of the insulating liquid dielectric is 1.2-1.8 times the volume of the porous carrier itself.

[0024] Thickness and porosity together determine the liquid storage capacity, deformation, and response speed of a material. Insufficient thickness and low porosity lead to inadequate liquid storage, making it difficult to replenish trace amounts of liquid phase lost during long-term operation, resulting in performance degradation. Conversely, excessive thickness and high porosity reduce the material's mechanical strength and structural stability, and the excessively long liquid phase conduction path under pressure decreases the dynamic response speed. A thickness of 1.0-3.0 mm and a porosity of 60%-85% achieve an optimal balance between liquid storage capacity, response speed, and mechanical strength. The corresponding saturated adsorption range ensures sufficient pore filling while avoiding surface flow problems caused by excessive liquid phase. Experimental verification shows that within this parameter range, a 1.0 mm thickness of meltblown polypropylene carrier is sufficient to meet the liquid phase requirements for interfacial transition; further increasing the thickness has no significant impact on output performance, confirming the rationality of the parameter design.

[0025] Furthermore, the friction working surface of the material is provided with a super-lubricating modified layer to reduce interfacial frictional resistance and eliminate dynamic wetting hysteresis of the three-phase contact line; the super-lubricating modified layer is composed of a polytetrafluoroethylene microporous membrane impregnated with an insulating liquid dielectric attached to the surface of the material.

[0026] Unmodified porous materials exhibit microscopic roughness due to fiber undulations on their surface. Initially, the liquid phase cannot fully wet the entire contact interface, resulting in an effective contact area smaller than the geometrically designed area. The material requires multiple operating cycles to reach steady-state output, exhibiting dynamic wetting hysteresis, which is detrimental to the response and perception of instantaneous signals. The super-lubricating modified layer, through the capillary action of a micron-level pore network, pre-saturates the insulating liquid dielectric, forming a continuous and uniform fluid lubricating film on the surface, transforming the original solid-liquid interface into a liquid-liquid interface. Its pre-wetting mechanism completely eliminates the dynamic hysteresis of the three-phase contact line, enabling the material to reach steady-state output within three operating cycles after startup, significantly improving response speed. Simultaneously, the fluid lubricating layer significantly reduces the interfacial friction coefficient, minimizing material wear during reciprocating motion and effectively extending service life.

[0027] Furthermore, the material is applied to an underwater triboelectric nanogenerator, where it acts as a friction layer to achieve electrical energy output through a liquid-mediated interface conversion mechanism.

[0028] This material can serve as a general-purpose underwater friction layer, adaptable to various triboelectric nanogenerator structures. In planar sliding mode, the material releases a liquid phase under shear force, achieving a large-area interface transition; in contact-separation mode, the material releases a liquid phase under normal pressure, achieving a vertical contact interface transition; in spherical rolling mode, the material continuously releases a liquid phase under compression during rolling, achieving a full-circumferential interface transition. Compared to traditional pure solid friction layers, underwater generators using this material can achieve several times higher output performance and significantly enhanced long-term operational stability, providing a core material solution for various underwater energy harvesting and self-powered sensor devices.

[0029] Correspondingly, the present invention also provides a method for preparing the above-mentioned solid-liquid composite friction material, the core process steps of which are as follows:

[0030] First, the hydrophobic and oleophilic porous carrier is pretreated by cutting it to the target size and cleaning its surface to remove impurities and dust, ensuring surface cleanliness and dimensional consistency. Then, the carrier is completely immersed in an insulating liquid dielectric and allowed to stand at room temperature and atmospheric pressure, allowing the liquid phase to fully penetrate the three-dimensional porous network under capillary action until adsorption saturation is achieved. Finally, the carrier is removed, excess liquid is removed from the surface, and the surface liquid film thickness is controlled to be uniform, thus obtaining the solid-liquid composite friction material. This preparation method is simple, with controllable parameters, requires no complex equipment or harsh environments, is suitable for large-scale batch production, and produces products with good performance consistency.

[0031] The corresponding beneficial effects are: ① It achieves stable confinement of the liquid phase medium at the material structure level, significantly improving the resistance to water flow erosion and enhancing long-term operational stability compared to traditional open liquid bridge structures, thus fundamentally solving the industry pain point of easy liquid phase loss; ② It completely eliminates the electrostatic shielding effect of the underwater double electric layer, greatly improving charge output performance, far superior to pure solid friction materials under the same conditions, and the power generation efficiency is close to that in air; ③ It has good dynamic response reversibility, can adapt to various working modes such as sliding, contact-separation, and rolling, has wide environmental adaptability, and can be applied to underwater triboelectric nanogenerators of various structures; ④ The preparation process is simple and controllable, the raw material cost is low, no complex equipment is required, it is suitable for large-scale industrial production, and has excellent engineering application potential.

[0032] Furthermore, the static immersion time is 20-40 minutes, and the immersion environment is room temperature and normal pressure.

[0033] Impregnation time is a key process parameter for ensuring saturated adsorption in the pores. If the impregnation time is too short, the liquid phase cannot fully penetrate deep into the pore network, leaving residual air bubbles and resulting in insufficient effective liquid storage, low output performance, and poor stability. Conversely, if the impregnation time is too long, it reduces production efficiency and increases preparation costs. An impregnation time of 20-40 minutes ensures that the three-dimensional pore network is completely filled with the liquid phase, achieving saturated adsorption, while maintaining production efficiency. The room temperature and atmospheric pressure process eliminates the need for heating or pressurization equipment, resulting in low preparation costs, simple operation, and suitability for large-scale batch production. It also avoids the damage to the porous carrier structure and the properties of the liquid medium caused by high temperature and high pressure.

[0034] Furthermore, filter paper adsorption is used to remove excess liquid from the carrier surface, ensuring a uniform and consistent surface liquid film thickness.

[0035] Excessive free liquid phase adheres to the surface of the carrier after impregnation saturation. If used directly, this free liquid phase will rapidly diffuse and dissipate underwater, causing initial performance fluctuations and easily contaminating the working environment. Filter paper adsorption is a gentle and controllable post-treatment method. It uses the capillary force of the filter paper to uniformly remove surface liquid, retaining only the bound liquid phase within the pores and an extremely thin surface wetting layer, ensuring a uniform surface condition. This method is simple to operate, highly controllable, and effectively improves the performance consistency between batches of materials, avoiding initial output instability caused by excessive surface liquid phase.

[0036] This invention can be used as a core friction layer in various underwater triboelectric nanogenerators and underwater self-driven fluid sensors, adapting to multiple working modes such as sliding, contact-separation, and rolling. Compared with existing underwater triboelectric power generation materials, it has the following significant technological advancements:

[0037] First, it exhibits strong liquid-phase binding ability and excellent long-term stability. The insulating liquid phase is stably bound through a capillary adsorption mechanism of a three-dimensional porous network, fundamentally solving the problem of open liquid bridges being easily washed away by water flow. Experimental verification shows that after 5250 seconds of continuous operation in an open water flow environment, the transferred charge remains stably maintained at approximately 37.75 nC, with no significant performance degradation throughout the process. The mass loss after operation is less than 1%, and the service life is an order of magnitude longer than that of open liquid-phase solutions.

[0038] Second, it boasts highly efficient power generation, completely overcoming the double-layer shielding. Based on a liquid-mediated interface conversion mechanism, it can physically disrupt the double-layer structure, removing electrostatic shielding within 3cm. 2 The amount of charge transferred under the contact area can reach 38.67 nC, and the output performance is far superior to that of traditional pure solid underwater friction materials, approaching the level of power generation in air.

[0039] Third, it has wide adaptability and strong versatility. The material has reversible dynamic response characteristics and can be adapted to various working modes such as sliding, contact-separation, and rolling. It can be used in planar structure generators as well as generators with special structures such as curved surfaces and spheres, and can be widely used in various underwater energy harvesting and sensing scenarios.

[0040] Fourth, the preparation process is simple and has strong engineering applicability. It can be prepared by room temperature impregnation process, without the need for complex equipment and harsh conditions. The raw material cost is low, it can be mass-produced on a large scale, and the material properties are consistent, providing mature and reliable material support for the engineering application of underwater triboelectric nanogenerators. Attached Figure Description

[0041] To more clearly illustrate the embodiments of this technical solution, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this technical solution. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0042] Figure 1 This is a schematic diagram illustrating the application structure and working principle of the solid-liquid composite friction material of the present invention.

[0043] Figure 2 Characterization diagrams of the wettability of different porous support materials:

[0044] (a) The state and contact angle of water and liquid dielectric on meltblown PP;

[0045] (b) Photographs of the original meltblown PP and meltblown PP impregnated with liquid dielectric;

[0046] (c) Cross-sectional photographs of the original meltblown PP and liquid dielectric-impregnated samples (stained with methyl red);

[0047] (d) Photographs of meltblown PP impregnated with liquid dielectric in an aquatic environment.

[0048] Figure 3 Comparison of power generation performance of different porous carrier materials:

[0049] (a) Optical photographs of the adsorption behavior and wettability of liquid dielectrics in different samples;

[0050] (b) Characterization of water contact angle for different materials;

[0051] (c) Comparison of water contact angle data for different materials;

[0052] (d) ΔQ of devices impregnated with different liquid dielectrics;

[0053] (e) V of devices impregnated with different liquid dielectric materials OC .

[0054] Figure 4 A comparison chart of power generation performance for carriers of different thicknesses:

[0055] (a) The effect of meltblown PP thickness on output performance;

[0056] (b) The effect of PTFE microporous membrane thickness on output performance.

[0057] Figure 5 This is a graph showing the long-term operational stability of the solid-liquid composite friction material of the present invention. Detailed Implementation

[0058] The technical solutions of this technical solution will be clearly and completely described below with reference to the accompanying drawings in the embodiments of this technical solution. Obviously, the described embodiments are only a preferred embodiment of this technical solution, and not all embodiments. Based on the core concept of this technical solution and the following embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this technical solution.

[0059] It should be noted that these embodiments are provided to make the application thorough and complete, and to fully express the scope of the application to those skilled in the art. It should be observed that, unless otherwise specifically stated, the relative arrangement of components and steps, material composition, numerical expressions, and values ​​described in these embodiments should be interpreted as merely exemplary and not as limiting.

[0060] Example 1: Preparation of meltblown polypropylene-based solid-liquid composite friction material

[0061] This embodiment details the specific preparation process and parameters of the solid-liquid composite friction material under the preferred scheme.

[0062] (1) Experimental materials and instruments

[0063] The hydrophobic and oleophilic porous carrier used in the experiment was commercial meltblown polypropylene nonwoven fabric with an average fiber diameter of about 5 μm, a porosity of about 75%, and an initial thickness of 2.0 mm; the insulating liquid dielectric was perfluorotributylamine (FC-40) with a purity of 99%; and the experimental water was deionized water.

[0064] The main experimental instruments include: laser cutter, electronic analytical balance (accuracy 0.1mg), contact angle measuring instrument, vacuum drying oven, electrometer, and circulating water flow test platform.

[0065] (2) Preparation steps

[0066] ① Pretreatment: Use a laser cutting machine to cut meltblown polypropylene nonwoven fabric into 30mm×30mm square samples to ensure that the edges are neat and burr-free; place the sample in a vacuum drying oven and dry at 60℃ for 2 hours to remove surface-adsorbed moisture and volatile impurities; after taking it out, place it in a desiccator to cool to room temperature, weigh and record the initial mass.

[0067] ②Immersion adsorption: The dried meltblown polypropylene sample is completely immersed in a glass petri dish containing perfluorotributylamine, ensuring that the sample is completely covered by the liquid phase with no floating parts; it is left to stand at room temperature and normal pressure for 30 minutes to allow the liquid phase to fully penetrate into the three-dimensional fiber pore network under the action of capillary force until the adsorption saturation state is reached.

[0068] ③ Post-processing: Gently remove the saturated sample with tweezers, and gently attach clean filter paper to the upper and lower surfaces of the sample to absorb excess free liquid on the surface; avoid squeezing the sample during the operation to prevent the internal liquid phase from being squeezed out; repeatedly replace the filter paper until there are no obvious liquid droplets flowing on the surface, and the meltblown polypropylene-based solid-liquid composite friction material is obtained.

[0069] (3) Characterization of basic physical properties

[0070] Basic physical property tests were performed on the prepared materials:

[0071] Saturated adsorption capacity test: By weighing the mass difference before and after impregnation with an electronic balance, it was calculated that the saturated adsorption capacity of meltblown polypropylene for perfluorotributylamine per unit volume is about 1.5 times its own volume, which meets the design expectations.

[0072] Wettability characterization: The static water contact angle of the material surface was tested using a contact angle meter. The results showed that the water contact angle of the meltblown polypropylene matrix was about 138.4°, exhibiting strong hydrophobicity. After the addition of perfluorotributylamine, the droplets spread rapidly, and the contact angle approached 0°, confirming its excellent oleophilic properties.

[0073] Elastic deformation test: The material was compressed using a universal testing machine. The results showed that under 30% compressive strain, the material rebound rate was greater than 95% and there was no obvious plastic deformation, which confirmed its excellent elastic reversible deformation capability.

[0074] like Figure 1 As shown, the prepared solid-liquid composite friction material consists of a three-dimensional network of polypropylene fibers and perfluorotributylamine bound in the pores. When under pressure, the liquid phase permeates out to form a liquid film, and after the pressure is released, the liquid phase is drawn back into the pores. The dynamic process is reversible and stable.

[0075] Example 2: Comparative Examples of Different Porous Carrier Materials

[0076] This embodiment compares the performance differences of four different porous carrier materials to verify the rationality and creativity of carrier selection.

[0077] (1) Sample preparation

[0078] Four typical hydrophobic and oleophilic porous materials were selected as carriers to prepare composite friction materials: meltblown polypropylene (PP), polytetrafluoroethylene (PTFE) microporous membrane, polyurethane (PU) foam, and porous vacuum silicone (MAVS). All carrier samples were 30 mm × 30 mm in size and 2.0 mm in thickness. The impregnation process was performed using the same method as in Example 1, with a uniform impregnation time of 30 min and consistent post-treatment.

[0079] (2) Comparative test of wettability

[0080] The wettability of four carriers was systematically characterized, and the results are as follows: Figure 2 As shown:

[0081] Meltblown polypropylene: water contact angle 138.4°, fully wetted by perfluorotributylamine, balanced hydrophobic and oleophilic properties, and good pore connectivity of the fiber network.

[0082] PTFE microporous membrane: water contact angle 135.2°, good wettability of perfluorotributylamine, and optimal chemical stability, but with regular pores and small deformation;

[0083] Polyurethane foam: water contact angle 126.7°, relatively weak hydrophobicity, large pores and high liquid storage capacity, but average oil resistance;

[0084] Porous vacuum silicon: with a water contact angle of 142.1°, it has the strongest hydrophobicity, but the material is rigid and has almost no compressibility.

[0085] The wettability test results show that all four materials have hydrophobic and oleophilic properties and can achieve capillary binding of the insulating liquid phase. However, their structures and mechanical properties differ significantly, which will directly affect the final power generation performance.

[0086] (3) Comparative test of power generation performance

[0087] Four composite friction materials were respectively assembled onto the same sliding underwater triboelectric nanogenerator test platform. The opposite friction pair consisted of a polytetrafluoroethylene film with a contact area of ​​3 cm². 2 The sliding speed was 0.27 cm / s, and the output performance was tested in an underwater environment.

[0088] like Figure 3 As shown, there are significant differences in the amount of transferred charge among the four materials:

[0089] Meltblown polypropylene-based materials: have the highest charge transfer capacity, reaching 38.67 nC, and an open-circuit voltage of 53.59 V, exhibiting the best overall performance;

[0090] PTFE microporous membrane-based materials: the charge transfer capacity is about 29.75 nC, the output performance is second best, and the liquid phase release is limited due to insufficient deformation.

[0091] Polyurethane foam-based materials: The charge transfer capacity is approximately 18.3 nC, the output performance is moderate, and plastic deformation is prone to occur under long-term compression;

[0092] Porous vacuum silicon-based materials: The amount of transferred charge is only about 6.1 nC, and the output performance is the lowest. This is because the material is rigid and the pores hardly shrink under pressure, making it difficult for the liquid phase to seep out.

[0093] (4) Results Analysis

[0094] The core reason for the performance difference lies in the matching between the elastic deformation capability and pore structure of the carrier: the ultrafine fiber network of meltblown polypropylene possesses both good elasticity and suitable pore size. Under pressure, it can effectively extrude the liquid phase, and after depressurization, it quickly rebounds and reabsorbs, achieving optimal dynamic equilibrium, thus resulting in the best power generation performance. This comparative result confirms that not all hydrophobic and oleophilic porous materials can achieve excellent power generation performance. The mechanical properties and pore structure design of the carrier are one of the core innovations of this material, and their nature is not obvious.

[0095] Example 3: Comparative Examples of Different Insulating Liquid Dielectrics

[0096] This embodiment compares the performance differences of seven different insulating liquid media to verify the rationality of liquid phase medium selection.

[0097] (1) Sample preparation

[0098] Using meltblown polypropylene as a uniform carrier, seven insulating liquids were selected for impregnation preparation, including: perfluorotributylamine, perfluorooctane, liquid paraffin, n-hexadecane, methyl silicone oil, ethyl silicone oil, and olive oil. All sample preparation processes were completely identical, with an impregnation time of 30 minutes, and all floating liquid was absorbed using filter paper.

[0099] (2) Comparison of interface features

[0100] Observation of the interfacial behavior of different liquid phases on the polytetrafluoroethylene (PTFE) mating surface:

[0101] Perfluorinated liquids: have clear interface boundaries, leave very little residue on the surface after reciprocating motion, and the liquid film can move synchronously with the liquid carrier;

[0102] Alkane and silicone oil: The interface boundary is relatively clear, with slight residues. The residue gradually accumulates after continuous operation.

[0103] Olive oil: It has high viscosity and easily spreads and remains on solid surfaces. After several cycles, it forms a continuous oil film on the rubbing surface.

[0104] (3) Comparison of power generation performance

[0105] The output performance of seven materials was tested under the same test conditions. The results showed that perfluorotributylamine had the highest output, with a charge transfer of about 38.67 nC; perfluorooctane was the second highest, with a charge transfer of about 32.4 nC; alkanes and silicone oils were in the middle, with charge transfers between 15-25 nC; olive oil had the lowest output, with a charge transfer of only about 6 nC.

[0106] The performance differences stem primarily from two factors: First, the difference in dielectric constant. Perfluorinated liquids exhibit the lowest dielectric constant, minimal interfacial polarization loss, and the highest charge transfer efficiency; olive oil, on the other hand, has the highest dielectric constant, high polarization loss, and poor output performance. Second, the difference in interfacial residue. Olive oil has high viscosity and significant residue, and the persistent oil film forms a permanent shield, leading to rapid output degradation; perfluorotributylamine exhibits minimal residue and the best output stability. This comparative result confirms that perfluorotributylamine is the optimal liquid phase choice for this material system, demonstrating the innovative design of the material composition matching.

[0107] Example 4: Performance Comparison of Carriers with Different Thicknesses

[0108] This embodiment verifies the influence of carrier thickness on material properties and optimizes the range of thickness parameters.

[0109] (2) Sample preparation

[0110] Meltblown polypropylene was used as the carrier to prepare samples of three different thicknesses: 1.0 mm, 2.0 mm, and 3.0 mm. Solid-liquid composite friction materials were prepared using the same impregnation and post-treatment processes. Simultaneously, PTFE microporous membrane samples of corresponding thicknesses were prepared as controls.

[0111] (2) Liquid storage volume test

[0112] The saturated adsorption capacity of samples with different thicknesses was measured by weighing. The results showed that the total liquid storage capacity of the material increased linearly with increasing thickness. The liquid storage capacity of the 1.0 mm sample was approximately 52% of that of the 2.0 mm sample, and the liquid storage capacity of the 3.0 mm sample was approximately 1.48 times that of the 2.0 mm sample. Theoretically, thicker materials can provide more sufficient liquid phase storage, which is beneficial for long-term operation.

[0113] (3) Comparison of power generation performance

[0114] The output performance was tested under the same sliding test conditions, and the results are as follows: Figure 4 As shown:

[0115] For meltblown polypropylene series, the transferred charge amounts for 1.0mm, 2.0mm, and 3.0mm thicknesses are 37.9nC, 38.67nC, and 38.2nC, respectively, with minimal differences. This indicates that the liquid storage capacity of a 1.0mm thickness is sufficient to meet the liquid phase requirements for a single interface transition, and further increasing the thickness will not improve output performance.

[0116] PTFE microporous membrane series: 1.0mm thickness outputs approximately 18.6nC, 2.0mm thickness outputs approximately 29.75nC, with performance significantly improving with increasing thickness. This is because PTFE microporous membranes have small deformation; at thinner thicknesses, the liquid storage capacity is insufficient, limiting the liquid phase release. Increasing the thickness increases the total liquid storage capacity, which can replenish the liquid phase consumed at the interface.

[0117] (4) Conclusion of parameter optimization

[0118] For the preferred meltblown polypropylene system, thicknesses of 1.0-3.0 mm can meet the application requirements. Considering both performance and cost, 1.0-2.0 mm is the optimal thickness range. This parameter pattern provides a quantitative design basis for the engineering application of materials, allowing for flexible selection based on specific scenarios.

[0119] Example 5: Solid-liquid composite friction material with super-lubricating surface modification

[0120] This embodiment verifies the effect of superlubricity modification on the material's start-up response characteristics.

[0121] (1) Preparation of modified samples

[0122] On the surface of the meltblown polypropylene-based composite friction material prepared in Example 1, a polytetrafluoroethylene microporous film with an average pore size of 10 μm is flatly attached, and the film is tightly bonded to the substrate without bubbles; then a small amount of perfluorotributylamine is added to fully wet and saturate the microporous film, and a continuous fluid lubrication layer is formed on the surface, thus obtaining the super-lubricating modified solid-liquid composite friction material.

[0123] (2) Performance comparison during startup

[0124] Under the same sliding test conditions, compare the start-up phase output characteristics of unmodified and modified materials:

[0125] Unmodified material: The initial stage of charge transfer is about 30.2 nC, which gradually increases with the increase of the operating cycle, and reaches a steady state value of 38.67 nC after about 12 cycles, showing obvious dynamic wetting hysteresis.

[0126] Modified material: The amount of charge transferred in the third cycle after startup reaches about 37.8 nC, and it quickly enters steady-state output without obvious rising transition stage.

[0127] (3) Effect Analysis

[0128] The super-lubricating modified layer, through a pre-wetting mechanism, forms a uniform liquid-phase lubricating film on the contact surface, eliminating the problem of insufficient local wetting caused by micro-roughness and completely breaking the hysteresis effect of the three-phase contact line, enabling full interface transition immediately after material startup. This modification scheme can significantly improve the material's response speed, making it particularly suitable for applications with high startup performance requirements, such as self-driven sensing. Simultaneously, the fluid lubrication layer can reduce the interfacial friction coefficient by approximately 40%, effectively reducing material wear and extending service life.

[0129] Example 6: Comprehensive Test of Power Generation Performance of Solid-Liquid Composite Friction Material

[0130] This embodiment systematically tests the power generation performance of the material under different working modes and conditions, comprehensively verifying the applicability of the material.

[0131] (1) Sliding mode performance test

[0132] The material was assembled onto a horizontal sliding test platform. The contact surface was a polytetrafluoroethylene film with a contact area of ​​3 cm². 2 Underwater environment testing.

[0133] The output performance was tested at different sliding speeds: at a sliding speed of 0.1 m / s, the transferred charge was approximately 36.2 nC; at a speed of 0.27 m / s, the transferred charge was approximately 38.67 nC; and at a speed of 0.5 m / s, the transferred charge was approximately 37.5 nC. The results show that the material's output performance remains stable over a wide speed range, and the liquid phase release and reabsorption can respond synchronously to the motion speed, exhibiting good speed adaptability.

[0134] (2) Contact-separation mode performance test

[0135] The material was assembled on a vertical contact-separation test platform to test its output performance under normal pressure.

[0136] Test results show that when the contact force is 5N, the amount of transferred charge is approximately 22nC; when the contact force increases to 10N, the compression increases, the liquid phase is released more fully, and the amount of transferred charge increases to 28nC; as the contact force continues to increase, the output tends to level off. These results confirm that the material can effectively achieve interface conversion power generation under positive pressure, adapting to the contact-separation working mode.

[0137] (3) Comparison test with pure solid materials

[0138] Under identical testing conditions, the underwater output performance of pure meltblown polypropylene solid friction material was tested, and the results showed that its transferred charge was only about 7.3 nC. The output performance of the solid-liquid composite friction material of this invention is about 5.3 times that of the pure solid material, with an extremely significant improvement effect. This fully demonstrates the great technical advantages of this material in overcoming the double-layer shielding and improving underwater output, and it possesses outstanding substantive characteristics and significant technological progress.

[0139] Example 7: Long-term stability test of solid-liquid composite friction material

[0140] This embodiment verifies the performance stability and liquid phase retention capability of the material during long-term continuous operation.

[0141] (1) Test Plan

[0142] A meltblown polypropylene-based solid-liquid composite friction material sample was assembled on a sliding test platform and subjected to a long-term continuous test in an open circulating water environment. The total test duration was 5250 seconds, and the change in transferred charge was monitored in real time using an electrometer throughout the test. The water temperature and flow velocity were kept constant to simulate real underwater working conditions.

[0143] (2) Results of performance changes

[0144] like Figure 5 As shown, the test results are as follows:

[0145] In the initial stage of testing (0-500s): the amount of charge transferred by the material stabilized at around 38.5nC, and the output was stable;

[0146] Mid-test period (around 2000s): The transferred charge was approximately 38.1 nC, showing only a slight decrease from the initial stage, with a decay rate of less than 1.1%.

[0147] At the end of the test (5250s): the amount of transferred charge remained stable at around 37.75nC, with no obvious trend of sudden performance drop throughout the test, and the cumulative decay was only about 2%.

[0148] (3) Verification of liquid phase retention capability

[0149] After the test, the material sample was removed, the surface moisture was gently wiped dry, and it was weighed. The weight was compared with the initial saturated mass to calculate the liquid phase mass loss rate. The results showed that after 5250 s of continuous operation, the internal liquid phase mass loss of the material was less than 1%, confirming that the capillary binding effect of the three-dimensional porous network can effectively resist water erosion and has excellent liquid phase retention ability.

[0150] Morphological observation of the material revealed that the fiber network structure was intact, with no obvious damage or plastic deformation, confirming that the material possesses excellent fatigue resistance and structural stability.

[0151] (4) Long-term immersion stability verification

[0152] The material sample was immersed in deionized water for 30 days. After removal, its power generation performance was tested. The results showed that the transferred charge could still reach more than 95% of the initial value, with no significant performance degradation. This result confirms that the material can maintain structural and performance stability even after long-term underwater immersion, and has the reliability for long-term service.

[0153] All aspects not detailed in this invention are conventional technical means known to those skilled in the art.

[0154] The above content shows and describes the basic principles, main features, and beneficial effects of this technical solution. The above description is merely a preferred embodiment of this technical solution and is not intended to limit the scope of this technical solution. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this technical solution should be included within the protection scope of this technical solution.

Claims

1. A solid-liquid composite friction material for underwater triboelectric power generation, characterized in that, Including hydrophobic and oleophilic porous carriers and insulating liquid dielectrics; The insulating liquid dielectric is adsorbed inside the three-dimensional pore network of the hydrophobic and oleophilic porous carrier and is bound in the pore structure by capillary force. When the material is compressed, the pores shrink and deform, and the insulating liquid dielectric seeps out to the material surface to form a continuous liquid film. After the pressure is removed, the pores rebound, and the insulating liquid dielectric is drawn back into the pores under the action of capillary force.

2. The solid-liquid composite friction material for underwater triboelectric power generation according to claim 1, characterized in that, The hydrophobic and oleophilic porous carrier is one of meltblown polypropylene porous network, polytetrafluoroethylene microporous membrane, and polyurethane foam.

3. The solid-liquid composite friction material for underwater triboelectric power generation according to claim 2, characterized in that, The insulating liquid dielectric is a perfluorinated insulating liquid that is immiscible with water, preferably perfluorotributylamine.

4. The solid-liquid composite friction material for underwater triboelectric power generation according to any one of claims 1-3, characterized in that, The hydrophobic and oleophilic porous carrier has a static water contact angle greater than 120° and a contact angle with the insulating liquid dielectric approaching 0°.

5. The solid-liquid composite friction material for underwater triboelectric power generation according to claim 4, characterized in that, The thickness of the hydrophobic and oleophilic porous carrier is 1.0-3.0 mm, and the porosity is 60%-85%; the saturated adsorption capacity of the insulating liquid dielectric is 1.2-1.8 times the volume of the porous carrier itself.

6. The solid-liquid composite friction material for underwater triboelectric power generation according to claim 5, characterized in that, The friction working surface of the material is provided with a super-lubricating modified layer to reduce interfacial frictional resistance and eliminate dynamic wetting hysteresis of the three-phase contact line.

7. The solid-liquid composite friction material for underwater triboelectric power generation according to claim 6, characterized in that, The material is used in underwater triboelectric nanogenerators, where it acts as a friction layer to achieve electrical energy output through a liquid-mediated interface conversion mechanism.

8. A method for preparing the solid-liquid composite friction material for underwater triboelectric power generation as described in claim 1, characterized in that, Includes the following steps: (1) Pretreatment: Cut the hydrophobic and oleophilic porous carrier to the preset size and clean it to remove surface impurities and dust; (2) Impregnation adsorption: The pretreated hydrophobic and oleophilic porous carrier is completely immersed in an insulating liquid dielectric and left to stand until the three-dimensional pore network reaches adsorption saturation. (3) Post-processing: Remove the porous carrier that is saturated with adsorption, remove the excess liquid on the surface, and obtain the solid-liquid composite friction material.

9. The preparation method according to claim 8, characterized in that, The static immersion time is 20-40 minutes, and the immersion environment is room temperature and normal pressure.

10. The preparation method according to claim 9, characterized in that, Excess liquid on the carrier surface is removed by adsorption using filter paper, ensuring a uniform and consistent liquid film thickness on the surface.